Experimental and numerical investigation of chloride-induced reinforcement corrosion and mortar cover cracking. (August 2020) - Chen, Junyu; Zhang, Weiping; Tang, Zhijie; Huang, Qinghua
Abstract: To investigate the time-varying progress of chloride-induced reinforcement corrosion and cover cracking, the authors embedded mortar specimens with side-located rebars and corner-located rebars. These specimens were exposed to a chloride contaminated environment to accelerate the corrosion process. This study focuses on the chloride ions penetration, corrosion products accumulation and surface crack propagation, and proves that the circumferential corrosion profile of steel bars is time-dependent. Considering the interaction between corrosion propagation and crack growth, a numerical model was developed by combining chloride diffusion law and electrochemical theory. The comparison between the predicted and measured evolution of rust layer distribution and surface crack width indicates that the modified model can simulate the process of chloride-induced rebar corrosion and mortar cover cracking reasonably. Finally, the simulation of mortar cover cracking induced by different corrosion profiles demonstrate that earlier cracking of mortar cover and faster development of surface cracks can be observed under the time-varying non-uniform corrosion condition. In addition, wedge-shaped cracks are more prone to occur as cover thickness decreases, and the delaying effect on the surface cracking time is more noticeable with the increase of interface transition zone (ITZ) thickness when using the authors' time-dependent non-uniform corrosion model. Highlights: Experimental study chloride-induced rebar corrosion and mortar cover cracking. Modified the time-dependent non-uniform corrosion model considering interaction effect. Revealed non-uniform corrosion process of steel bar under a chloride attack environment.